Factors affecting Pan Evaporation in the hyper arid region of the Sudan and the quality of the data of National Institute of Desert Studies meteorological station - , admin (Gezira Journal of Agricultural Science, 2016)
Evaporation is an important climate element for agricultural production, particularly in the hyper arid and arid regions where irrigation water becomes the most limiting factor in terms of availability and cost (Mohamed, 2015).The magnitude of evaporation depends on other climate elements like air temperature, relative humidity, wind speed and solar radiation (Liu et al ., 2011; Mohamed and Mohamed, 2011).The water needs of crops, on the other hand, depends on evapotranspiration and on the crop factor, where evapotranspiration includes both evaporation and transpiration (Brouwer and Heibloem,1986).       Determination of the exact crop water requirement depends on the correct measurements and estimation of evapotranspiration. Precise estimation of evapotranspiration is vital in agriculture and hydrology (ElAlafandi and Abdrabbo, 2015). There are numerous methods for the estimation of evapotranspiration including energy budget, aerodynamic and numerical methods in addition to various methods of measurements including atmometers, lysimeters, Class (A) Pan and Piche tube. One of the simplest and reliable methods of measurements is the use of Class (A) pan. Because of the importance of these measurements, the National Institute of Desert Studies (NIDS)established in 2008 a meteorological station within its experimental farm, (17.92 ° N, 31.17 ◦ E).The station measures air and soil temperatures; wet and dry bulb temperatures; wind speed and direction, rainfall, Piche evaporation and Class Pan evaporation.